Interview of Maxwell Britton by Raimund E. Goerler - Britton, Maxwell (Byrd Polar Research Center Archival Program, 2005)
Benjamin Harrison Smith, pp. 4 Edgar Nelson Transeau, pp. 10 William C. Steere, pp. 13, 17, 24 Laurence Irving, pp. 15, 17 Ira Wiggins, pp. 17, 24 Max Brewer, pp. 17, 23, 39, 41, 44-45, 47-49, 55-56, 60-61, 65, 67, 72-73, 77, 79-84 Vilhjalmur Stefensson, pp. 18 Sir Hubert Wilkins, pp. 18 Bernt Balchen, pp. 19 John Reed, pp. 19 Dr. Louis Quam, pp. 19, 22, 24, 26, 29, 31, 39, 51, 55-56, 64, 75 Max Byrd, pp. 23 Art Lachenbruch, pp. 23, 73-74 Waldo Lyon, pp. 35-36, 38, 61, 68-69 Rosen Bennett, pp. 38 Max Fisher, pp. 47 Joe Fletcher, pp. 53-54 Bert Crary, pp. 53 Father Tom Cunningham, pp. 55 Noel Ween, pp. 60 Ron McGregor, pp. 66 George McGinnitie, pp. 67 Nettie McGinnitie, pp. 67 George Grits, pp. 72 Vice President Agnew, pp. 74-75 Braggett Hersey, pp. 75 Brian Shoemaker, pp. 81 John Schindler, pp. 81, 83-84 John Kelly, pp. 81 Kenny _________pp. 84, 86 Pete_______pp. 86 Max Ogiak, pp. 86-87 _______Ograk-McCain, pp. 87 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Dr_Maxwell_Britton_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Dr_Maxwell_Britton_2.mp3 Audio Part 3: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Dr_Maxwell_Britton_3.mp3 Dr. Britton was born in 1912 in a small coal mining town in southern Indiana. He summarized the quality of his high school science courses as poor; for example, a meter stick was the only piece of equipment in the physics course. A botany professor at Indiana State Teachers College stimulated Dr. Britton’s interest in science. An undergraduate assistantship helped pay his college expenses during the Great Depression (1930s). After completing his Master’s degree at the Ohio State University, he enrolled at Northwestern University for his PhD. Dr. Transeau (OSU) encouraged him to become an ecologist. After army service, a colleague at the University of Michigan told him of work with the National Arctic Research Laboratory (NARL) at Barrow. Dr. Britton preferred cold ...